PENGARUH PENGAWASAN DAN MOTIVASI TERHADAP KEPUASAN KERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA SURAKARTA - Afifah, Nurul (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
The objectives of this research are to investigate: (1) to a partially significant effect of the work supervision and the work motivation on the work satisfaction of the staff of the Department of Education, Youth, and Sports of Surakarta City (2) and to a simultaneously significant effect of the work supervision and the work motivation on the work satisfaction of the staff of the Department of Education, Youth, and Sports of Surakarta City. This research used the descriptive quantitative research method. Its population was all of the staffs of the Office of Education, Youth, and Sports of Surakarta City as many as 80 persons. The samples of the research consisted of 49 persons or 60% of the population. They were taken by using the proportional random sampling technique. The data of the research were gathered through questionnaire, and they were then statistically analyzed by using the correlational and multiple regression analyses. The results of the research are as follows: (1) there is a partially significant effect of the work supervision and the work motivation on the work satisfaction (2) and there is a simultaneously significant effect of the work supervision and the work motivation on the work satisfaction. Each independent variable has a contribution to the dependent variable. The relative contribution of the work supervision to the work satisfaction is 43.60%, and that of the work motivation to the work satisfaction is 56.40%. Furthermore, the effective contribution of the work supervision to the work satisfaction is 29.33%, and that of the work motivation to the work satisfaction is 37.95%.Keywords: supervision, motivation, and work satisfaction